Penguatan Kader Tani Sebagai Upaya Pencegahan Stunting Desa Alue Ambang Kabupaten Aceh Jaya - Agustinur; Jasmi; Muhammad Jalil; Dewi Fithria; Muhammad Afrillah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Stunting has become one of the national issues that are of concern to the government and requires an immediate solution. One of the districts in Aceh Jaya that is targeted for stunting prevention is Teunom. One of the efforts that can be done as a series of stunting prevention efforts in Aceh Jaya is to mobilize community farmer groups to pay attention to fulfilling family nutrition. This service is carried out to strengthen farmer cadres in Alue Ambang, Teunom Aceh Jaya in order to support the program to fulfill family food needs through the use of household yards. The activity was carried out for 2 days which included counseling or socializing the importance of stunting prevention and fulfilling family food nutrition and organizing farmer cadres in Alue Ambang village. The result of this activity was the formation of farmer cadre organizations and the community became more aware of the functions and duties of farmer cadres to support stunting prevention efforts in Alue Ambang village.